Hepatitis B small surface antigen particles are octahedral. - Gilbert, R; Beales, L; Blond, D; Simon, M; Lin, B; Chisari, F; Stuart, D; Rowlands, D (2005)
The infectious component of hepatitis B (HB) virus (HBV), the Dane particle, has a diameter of approximately 44 nm and consists of a double-layered capsid particle enclosing a circular, incomplete double-stranded DNA genome. The outer capsid layer is formed from the HB surface antigen (HBsAg) and lipid, whereas the inner layer is formed from the HB core Ag assembled into an icosahedral structure. During chronic infection HBsAg is expressed in large excess as noninfectious quasispherical particles and tubules with approximately 22-nm diameter. Here, we report cryo-EM reconstructions of spherical HBsAg particles at approximately 12-A resolution. We show that the particles possess different diameters and have separated them into two predominant populations, both of which have octahedral symmetry. Despite their differing diameters, the two forms of the particle have the same mass and are built through conformational switching of the same building block, a dimer of HBsAg. We propose that this conformational switching, combined with interactions with the underlying core, leads to the formation of HBV Dane particles of different sizes, dictated by the symmetry of the icosahedral core.